Beatitudes and Woes as a Manifesto of the Kingdom of God. A Study on a Second Temple Jewish and Early Christian Literary Form. - Barbotti, Irene (Trinity College Dublin. School of Religion. Discipline of Religions and Theology, 2026)
The present research investigates the diffusion of paired beatitudes and woes in Second Temple Jewish and early Christian literature. It argues that two initially distinct literary forms (the beatitude and the woe) gave rise during the Second Temple period to a new composite literary form, namely the coupling of beatitude and woe. This form was used to identify and distinguish two opposing categories of individuals: on the one hand, the righteous, declared "blissful" and, on the other, the wicked, to whom "woes" are announced. These groups are portrayed as already oriented toward eschatological reward and punishment respectively, thus anticipating in the present the anthropological distinction between righteous and wicked established by the divine judgment. The study traces a trajectory spanning approximately six centuries (mid-2nd century BCE to 4th century CE). It moves from early Jewish texts (e.g., the Epistle of Enoch, 4Q185, and 2 Baruch) to the New Testament (the gospels of Matthew and Luke, and Revelation) and finally to a broad range of early Christian writings (the gospel of Thomas, Didache, the Pseudo-Clementine Homilies, the Book of Thomas the Contender and the Apostolic Constitutions and Canons). This research is based on a systematic application of the Formgeschichte, a methodology based on the eidographic identification of literary genres, forms, and formulas, and on the attempt to reconstructing their original context of use. Besides the thorough application of this methodology to identify and study the couplings of beatitudes and woes in this literature, this research also entails a combination of both diachronic and synchronic approaches. On the one hand, a diachronic approach has been used to reflect on the literary sources adopted by the documents here investigated (e.g. the adoption of the "Two-Source Hypothesis" in the analysis of the gospels of Matthew and Luke), or to trace a development in the use of the literary form itself, i.e. the coupling of beatitude and woe, over centuries. On the other hand, a synchronic approach has been adopted to evaluate those cases in which couplings of beatitude and woe are strategically placed to play a structural function in the overall texts (e.g. the gospel of Matthew, Revelation and Second Baruch), thus requesting an interpretive approach to the document as a whole. The thesis articulates into three main parts. Part I sets the methodological grounding of the research, tracing a history of the development of beatitude and woe and distinct and separate literary forms and exploring their merging during the Second Temple period. Part II focuses on the Synoptic tradition, developing the Q-Catalogue Hypothesis (= Q-CH). This latter is grounded in the "Two-Source Hypothesis," and posits an original Q-catalogue of opposite beatitudes and woes as a possible explanation to the textual parallels between the collections of beatitudes and woes attested in Matt 5:3-12; 23:13-36; and Luke 6:20-26; 11:39-52. Notably, the development of the Q-CH does not only imply insights about the Q-catalogue itself, but it also entails reflections about the different theological stances displayed by Matthew and Luke in their reception of this hypothetical source. These involve the Matthean disposition of these collections of sayings at the beginning and at the end of Jesus' public life (cf. 5:3-12; 23:13-36), thus framing his preaching into antithetical announcements of eschatological reward and punishment; and the Lukan synthetic and community-oriented reworking of the original Q-catalogue in 6:20-26. Part III explores two different streams of specialization of this literary form, including the use of opposite beatitudes and woes to frame textual units, or the architecture of the overall text, as it happens in the gospel of Matthew, 2 Baruch and Revelation; and the consistent attribution of these couplings of sayings to Jesus in early Christian literature. Among the main outcomes of this research, there is the identification of a new literary form, typical of Second Temple Jewish and Early Christian writings, i.e. the coupling of beatitude and woe. The analysis of this latter takes advantage from the development of a diachronic application of the Formgeschichte, used to track the history of a literary form and its evolving Sitz im Leben through centuries. Moreover, the application of this methodology to different texts has allowed for the identification of new source-critical and hermeneutical keys to approach the passages in which this literary form occur. These findings include the hypothesis of a possible Q-catalogue behind the Matthean and Lukan collections of beatitudes and woes; the recognition of a theologically grounded structural use this literary form in Matthew, 2 Baruch, and Revelation; and the identification of a tradition that consistently attributes such couplings to Jesus in early Christian literature.
APPROVED
Keywords: New Testament; Second Temple Judaism; Beatitudes; Woes; Eschatology; Early Christian Literature; Form Criticsm